A pilot longitudinal study of anti‐Müllerian hormone levels throughout gestation in low risk pregnancy. Issue 8 (19th June 2018) - Freeman, Joshua R.; Whitcomb, Brian W.; Roy, Amrita; Bertone‐Johnson, Elizabeth R.; Reich, Nicholas G.; Healy, Andrew J.
Abstract: Background: Anti‐Mϋllerian hormone (AMH) plays an important role regulating ovarian sensitivity to follicle‐stimulating hormone and luteinizing hormone in folliculogenesis. Anti‐Mϋllerian hormone is well established as a biomarker of ovarian reserve but may also have utility in predicting pregnancy outcomes. Few studies have described AMH levels in pregnancy and, among those that have, most have used cross‐sectional study designs and are limited to participants seeking fertility treatment. Our aim was to analyze AMH longitudinally in low‐risk pregnancies. Methods: We conducted a prospective cohort study at Baystate Medical Center, a large tertiary care hospital in Springfield, MA, USA. We recruited women (n = 30) with low risk, singleton pregnancies, aged 18 to 35 years, with BMI between 18 and 40 kg/m 2, and without preexisting disease. Anti‐Mϋllerian hormone (pmol/L) was measured in plasma samples collected at 5 prenatal care visits throughout gestation. Results: Anti‐Mϋllerian hormone levels varied significantly over gestation (Friedman's analysis of variance, P value < .0001). At gestational weeks 7 to 10, average AMH was 36.7 pmol/L (standard error = 8.1) and at weeks 34 to 37 was 9.5 pmol/L (standard error = 1.9). Initial AMH varied between women, and an overall significant log‐linear decline was observed. Conclusions: Anti‐Mϋllerian hormone varies between women and declines exponentially during pregnancy. The biological mechanism of the heterogeneity of AMH decline over gestation is unclear. Future studies evaluating AMH throughout pregnancy that also assess gravid health and pregnancy outcomes are warranted.